Pengaruh Core Strengthening Exercise Terhadap Keseimbangan Statis Anak Usia 5-6 Tahun - Amaliyah, Miftahul Nur; , Edy Waspada, S. Fis., M. Kes; , Agus Widodo, S.Fis, M.Kes (2016)
Background: Static balance refers to the ability of the body to maintain equilibrium in a stationary position. Balance is needed to control the basic motor skills of children, especially for children aged 5-6 years to maximize its development phase to move up the next development phase. One of exercise that can be used to improve the balance of children aged 5-6 years is core strengthening exercise. Objective: To determine the effect of core strengthening exercise to static balance children age 5 to 6 year olds. Methods: The study was a quasi experiment with pre and post test with control group desaign, sample in the treatment group was given 4 weeks of core strengthening exercise with a frequency of 3 times a week, with a total sample of 60 children aged 5-6 years. Measurements using a pediatric reach static balance test. Data were analyzed using Paired Samples t-test to test the effect and Independent Sample t-test to test different effect. Results: There is a core strengthening exercise influence on the static balance after the performed statistical tests using paired sample t-test p-value obtained sitting and standing position 0,000 in the treatment group and 0,003 sitting position, standing 0,002 in the control group. Conclusion: There was effect core strengthening exercise for static balance children age 5-6 year olds. Keyword: Core Strengthening Exercise, Static Balance, Children Age 5-6 Year Olds.